GENERASI Z DAN TANTANGAN VALIDASI INFORMASI: STUDI KUALITATIF PADA MAHASISWA PENDIDIKAN IPS UIN JAKARTA - Naida Azzahra, Arif Saefudin, Muhammad Haekal Nugraha, Nurul Putri Arfitra, Meicca Javanisa Utami, (FKIP UMN ALWASHLIYAH, 2025)
The rapid growth of digital information flow requires Generation Z students to possess strong information validation skills in academic activities. This study aims to describe the information validation competence of Social Studies Education students at UIN Jakarta as representatives of Generation Z. The research employed a qualitative case study approach supported by simple quantitative data from questionnaires. Data were collected through in-depth interviews, observations, and documentation involving fifth-semester students selected by purposive sampling. Data analysis applied the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, display, and conclusion drawing. The findings indicate that students primarily rely on social media and scientific journals as their main sources, showing a high awareness of the importance of information verification. The study concludes that Generation Z’s information validation competence is relatively well-developed but requires further strengthening through digital literacy education. This research contributes to enriching digital literacy studies and advancing higher education strategies based on information literacy.